MODERNISASI PERADILAN TATA USAHA NEGARA DI ERA REVOLUSI INDUSTRI 4.0 UNTUK MENDORONG KEMAJUAN PERADABAN HUKUM INDONESIA - Supandi (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2019)
Information technology has changed all aspects of human life, including law and government. The transformation of conventional government into electronic government (e-government) is one of the public policy issues that dovelop continuosly in various countries all over the world. In exercising judicial power in Indonesia, Supreme Court has taken an initiative to develop public services through information technology networks by implementation of electronic court system. As one of the judicial institutions under the Supreme Court, the Administrative Court has also modernized the implementation of its duties to enforce law and justice. The modernizations in the Administrative Court include five issues that will be mainly discussed in this research, namely: (1) the development of the authority of the Administrative Court; (2) Progressive decisions in the Administrative Court; (3) Evolution of thought and work culture in the Administrative Court; (4) e-court, paperless and green courts; and (5) Electronic decision and electronic evidence in the Administrative Court.